Animal imagery in the book of Proverbs - Forti, Tova. (Vetus Testamentum, Supplements, 2008)
Any treatment of the figurative and symbolic function of animal imagery in biblical literature requires special attention to its contextual meaning and cultural evaluation. The present study aims to demonstrate how this is particularly true of the Book of Proverbs, in which faunal imageries serve as a didactic means for delving into the more obvious truths of human behavior. This book makes a methodological contribution toward understanding the didactic function of Proverb's animal imageries by offering an ongoing three-pronged analysis: a. Zoological identification and literary perception of the animal in the Bible; born Hermeneutic dynamics between the specific animal simile and its literary adaptation; c. Rhetorical function of the animal imagery within the conceptual framework of the Book of Proverbs.